Analysis of hybrid layer thickness, resin tag length and their correlation with microtensile bond strength using a total etch adhesive to intact dentin. - Anchieta, Rodolfo B; Oliveira, Fernanda G; Sundfeld, Renato Herman [UNESP]; Rahal, Vanessa; Machado, Lucas S; Alexandre, Rodrigo S; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Rocha, Eduardo Passos [UNESP] (My University, 2011)
The objective of this study was to evaluate the use of a two-step total etch and rinse adhesive, the correlation between the hyybrid layer thickness (HL) and bond strength (BS), and between resin tag length (RT) and bond strength in the same teeth, and also to evaluate the fracture patterns of the tested specimens. Ten human molars were used for the restorative procedure and then sectioned in two halves (mesio-distally). The materials used were Adper Single Bond 2, 3M ESPE, Ultra etch gel, Ultradent and Filtek Z250, 3M ESPE. One half were utilized to measure the HL thickness and RT length through light microscopy analysis (400x), and the other half was subject to a microtensile test to measure the BS. The fractured surfaces were analyzed by scanning electron microscopy and fracture patterns classified. The Pearson correlation test was applied (p = 0.05). The results of the analyses of each specimen then were correlated: mean HL thickness = 4.39 (0.48) microm, mean length of RT = 9.94 (1.69) microm, mean BS = 23.98 (10.24) MPa. A statistically significant correlation between HL thickness and bond strength was found (r = 0.93). The two step etch and rinse adhesive system, showed a strong correlation between HL thickness and bond strength. The most common fractures were adhesive, followed by cohesive in resin.
Keywords: dentin bonding agent; resin; tooth cement; dental bonding; dental procedure; dentin; human; in vitro study; materials testing; molar tooth; surface property; tensile strength; Dental Bonding; Dental Cements; Dental Stress Analysis; Dentin; Dentin-Bonding Agents; Humans; Materials Testing; Molar; Resins, Synthetic; Surface Properties; Tensile Strength